2014
DOI: 10.2174/1871527313666140612122929
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation: A New Treatment in Mood and Anxiety Disorders

Abstract: This article considered already existing studies about Deep Brain Stimulation in Mood and Anxiety Disorders. In particular, articles regarding Obsessive-Compulsive Disorder and Major Depression were mostly analyzed, due to the lack of researches about other types of Mood and Anxiety Disorders. We have concentrated on the target areas where Deep Brain Stimulation was most commonly applied, and on the effects this measure had on treatment-refractory patients. The obtained results showed that the stimulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…It is thus suggested that the striatum can be a therapeutic target for promoting SVZ neurogenesis. Clinically, this is achievable using deep brain stimulation (DBS) and brain-implanted devices of closed-loop technology (Krook-Magnuson et al, 2015; Mikell et al, 2016; Velasques et al, 2014). Other novel methods including optogenetics and pharmacogenetic may also have clinical potential of specific stimulation (Little and Brown, 2014; Peled, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is thus suggested that the striatum can be a therapeutic target for promoting SVZ neurogenesis. Clinically, this is achievable using deep brain stimulation (DBS) and brain-implanted devices of closed-loop technology (Krook-Magnuson et al, 2015; Mikell et al, 2016; Velasques et al, 2014). Other novel methods including optogenetics and pharmacogenetic may also have clinical potential of specific stimulation (Little and Brown, 2014; Peled, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…According to the current literature, NA DBS modulates the function of several brain (primarily cortical) areas including the CG cortex (Figure 1). It specifically causes activation in the ipsilateral CG cortex, and voltage-depended reduction of its blood oxygenation [16]. It also reverses anterior mid-CG cortex dysfunction [23] and decreases metabolism in the subgenual CG [24].…”
Section: Discussionmentioning
confidence: 99%
“…Deep brain stimulation (DBS) has proven efficacy in neurobehavioral disorders, works by modulation of cortico–striato–pallido–thalamo–cortical circuits implicated in these disorders [10], and is emerging as a promising powerful tool for the alleviation of targeted symptoms in treatment-resistant neuropsychiatric disorders. The major targets of neuropsychiatric DBS, for treating disorders such as treatment-resistant depression (TRD) and obsessive-compulsive disorder (OCD), include the NA and the CG cortex (especially the subcallosal/subgenual CG/Brodmann area 25 [8,11,12,13]) or CG subgenual white matter [8,10,11,12,13,14,15,16,17,18]. These targets seem to be safe [13], with positive influence on mood and anxiety disorders and sometimes complete remission of the symptoms [15,16], although in a small number of cases [13].…”
Section: Introductionmentioning
confidence: 99%
“…[116]. DBS can also be used in research studies of major depression [117,118] and other affective disorders [119], as well as in treatment of chronic pain [120,121], though none of these newer indications have been approved by FDA till now, which may probably due to high complication rates and side effects.…”
Section: Clinical Studies Of Deep Brain Stimulationmentioning
confidence: 99%